From Soldier to Civilian: A Review of Texas Veteran Reintegration Programs for Factors That Aid or Inhibit the Successful Transition of Newly-Discharged Military - Crain, Sarah N (ProQuest Dissertations & Theses, 2019)
The U.S. Census (2017) estimates that there are 1.6 million veterans in Texas. There are a significant number of government and nonprofit organizations that help veterans reintegrate into society. Asking professionals at these veteran nonprofit organizations who specialize in serving this population will determine what factors attribute to successes and failures in making the change from soldier to civilian. Surveying organizations allows for research beyond the literature for critical variables that assist veteran reintegration into civilian life. This study does not attempt to be an extensive list of all programs offered through nonprofits, but instead it seeks to determine key strengths by interviewing professionals that serve thousands of veterans throughout the State of Texas and asking those professionals what services, personal characteristics or other assets they have found to be beneficial for their clients during reintegration. A content analysis of these interviews suggests a consensus among the respondents about what assets can be focused upon to increase the likelihood of successful reintegration for the future. Respondents believed that there are client and program factors that limit success. The most common program limitations are lack of funding, a veteran mindset warrior ethos, and lack of marketing while the most common veteran limitations are veterans' attitudes and veterans' support systems. The literature on this subject goes back about thirteen years and this study confirms that veterans are still facing the same issues.